CODE SWITCHING USED BY THE STUDENTS IN EFL CLASSROOM INTERACTION - Heriyanti Tahang; Shobariah Ahmad; Rinda Hardianti; Ruslan Hasyim; St. Rahmaniah Bahrun (JLE: Journal of Literate of English Education Study Program, 2022)
This research aims at finding out the types of code-switching used by the students in the English as a foreign language classroom interaction. The research employed descriptive qualitative research design. The subjects were the students of English language education program. All of them used Papuan Malay language in their daily life but in class they used Indonesian language as mother tongue and English language as target language. The researcher findings that there are five types of code-switching that used by the students in EFL classroom interaction. Those Inter – sentential, Intra – sentential, and tag switching. For each type, the switch frequently used was as a clause, then as a word, and the last was as a sentence. They used them to clarify what they said because they tended to repeat or tried to translate the words again, and another reason was switching the words into the daily language was one of the ways to use to continue speaking. The impact of code-switching on TEFL was extremely beneficial since it may be utilized as a method or tactic in teaching English content, pushing students to talk, evaluating problems, and encouraging students to keep speaking in EFL classroom.